The early school leaving - Marina Torres, José Antonio (Avances en Supervisión Educativa, 2011)
A great amount of research on school-dropout has studied the different psychological, social and economic factors that have an influence on it. Nevertheless, since these data have not helped us solve the problem, the author proposes a new approach, consisting of explaining not school-leaving but school-attendance rather, and continuation of studies into further education.